The Effect of Resistance Training with Assisted Means According to Some Biomechanical Indicators on Developing the Accuracy of Smash Hit in Volleyball for Youth - Sajad Hashim Razzaq; Rezan Hassan Sattar; Layla hussen ali; Haider Sadiq Makki (Journal of Education and Sport Science, 2026)
The importance of this research lies in providing resistance training with assisted means for the technical performance, according to some biomechanical indicators, and its impact on the accuracy of the smash hit skill in volleyball, especially for the youth sample, who represent the basic pillar of the game, to ensure their learning of a technical performance based on a scientific basis, for this important skill and achieving more points and its impact on the result. The problem of the research was identified through following up on the developments in volleyball in general and the development of the smash hit skill in particular at the global and Arab levels, and its impact on determining the outcome of the match. The researchers observed that the technical level of this skill does not match the development and that there is a weakness and great fluctuation among young players in the level of accuracy of performance, which the researchers attribute to the lack of attention to improving the physical aspect according to the mechanical principles and rules, which is one of the most important problems facing those responsible for the training process. The objectives of the research were to prepare resistance training with assisted means according to some biomechanical variables to correct the accuracy of the smash hit in volleyball, to identify the statistical differences between the pre- and post-tests among some biomechanical variables to correct the accuracy of the smash hit in volleyball, and to identify the statistical differences between the pre- and post-tests for the accuracy of the smash hit in volleyball.The researchers used the experimental method with a one-group design, which is suitable for the problem to be researched, to complete the research process. The researchers identified the research population intentionally, who are the youth players (from the Volleyball Specialized Center in Dhi Qar Governorate, Shatra District), numbering (16) players, and the research sample was chosen, numbering (8) players, who represent (50%) of the original population. One of the most important conclusions is that the resistance training prepared by the researchers contributed to the development of some biomechanical variables for the smash hit.